P.194 In search of real-world neuroprotection in mechanical thrombectomy for ischemic stroke. (November 2021) - Mattingly, TK; Whyte, R; Kohli, GS; Susa, S; Bender, MT; Bhalla, T
Abstract : Background: The promise of neuroprotection for stroke remains elusive. Common medications in endovascular stroke thrombectomy have putative neuroprotective mechanisms in basic science literature. We evaluated our stroke registry for evidence that these medications have any impact on clinically meaningful outcome. Methods: A retrospective stroke thrombectomy database was evaluated for clinical and angiographic outcomes of patients receiving IV or IA tPA, Heparin, or Verapamil during procedure. Univariate analysis evaluated associations with periprocedure hemorrhage, recanalization, and functional outcomes. Results: 284 patients underwent mechanical thrombectomy over 2.75 years. For periprocedural hemorrhage, IV tPA (OR 0.457, CI 0.261-0.811, p=0.008) and Heparin (1.897, CI 1.112-3.205, p=0.019) had significant relationships. No medication had impact on favorable recanalization (TICI 2b/3). Heparin had a negative impact on 90day mRS 0-2 (OR 0.563, CI 0.348-0.901, p=0.023). Favorable recanalization remains associated with favorable outcomes at 90days (OR 2.066, CI 1.063-4.069, p=0.0361). Conclusions: While the adjunctive use of 3 commonly used periprocedural medications have a logical role in the mechanical thrombectomy eg IA tPA for clot lysis, they do not have clinical benefit that represents neuroprotection. Multivariate analysis may show more effect. A role for intraarterial neuroprotective agents exists given only 45% of patients in this series achieved functional independence.